Оптимальні умови роботи теплонасосних систем опалення з використанням акумульованої теплоти грунту - Безродний, М.К.; Притула, Н.О.; Гобова, М.О. (Энерготехнологии и ресурсосбережение, 2017)
Викладено методику визначення оптимальних умов роботи вертикального грунтового теплообмінника для теплонасосної системи низькотемпературного водяного опалення з використанням теплоти грунту, що забезпечують мінімум енергетичних затрат на вироблення теплоти. Изложена методика определения оптимальных условий работы вертикального грунтового теплообменника для теплонасосной системы низкотемпературного водяного отопления с использованием теплоты грунта, которые обеспечивают минимум энергетических затрат на выработку теплоты. The method of determination of optimal working conditions of vertical ground heat exchanger for heat pump low temperature water heating system, providing minimum energy cost for heat production is presented in this article. It was determined that there is an optimum speed of a heat carrier to which minimum total cost of electricity for heating system in a whole corresponds when using vertical probes for heat pump heating system.